Los procesos políticos en torno al saneamiento rural: el caso del SanToLiC en la India - Hueso, A.; Fernández-Baldor, A. (Revista Iberoamericana de Estudios de Desarrollo)
Against a backdrop of an ineffective rural sanitation campaign by the Indian Government, in the late 2000s several stakeholders tried to introduce an innovative participatory approach called Community-Led Total Sanitation (CLTS). However, these efforts faced complicated political processes that determined their success. In this research, these processes are analyzed, using Budni block in the state of Madhya Pradesh as a case study, with a theoretical framework focused on political narratives, agents and interests. The efforts to introduce CLTS in Madhya Pradesh were sterile, as they jeopardised the interests of important agents. Locally, Budni block was an exception. Through a collaboration between two key agents —a high level block Government officer and UNICEF— who were able to promote the CLTS narrative successfully and to manage strategically the interests of those involved, it was possible to implement a coherent campaign coherent CLTS sanitation.